Disease Characteristics, Care-Seeking Behavior, and Outcomes Associated With the Use of AYUSH-64 in COVID-19 Patients in Home Isolation in India: A Community-Based Cross-Sectional Analysis - Narayanam Srikanth; Adarsh Kumar; Bhogavalli Chandrasekhararao; Richa Singhal; Babita Yadav; Shruti Khanduri; Sophia Jameela; Amit Kumar Rai; Arunabh Tripathi; Rakesh Rana; Azeem Ahmad; Bhagwan Sahai Sharma; et al. (Frontiers Media S.A., 2022)
BackgroundDuring the second wave of the COVID-19 pandemic in India, the Ministry of Ayush conducted a community study to provide therapeutic care to patients with asymptomatic, mild, and moderate COVID-19 in home isolation based on the empirical evidence generated on the efficacy of AYUSH-64 in COVID-19.ObjectiveTo document disease characteristics, care-seeking behavior, and outcomes in patients with asymptomatic, mild, or moderate COVID-19 in home isolation who used AYUSH-64 for COVID-19.MethodsCross-sectional analysis of the data generated through a community study conducted in India from 08 May to 31 August 2021 was performed to study the disease characteristics, care-seeking behavior during home isolation, clinical outcomes, adverse events, and the association between various risk factors and clinical recovery during the study period. The data were collected through semi-structured questionnaires, available in electronic data collection format at the baseline, 7, 14, and 21 days. A logistic regression was performed to explore the relationship between relevant variables and clinical recovery.ResultsData from 64,642 participants were analyzed for baseline assessment, and final analysis was done for 49,770 participants. The mean age of the enrolled participants was 38.8 ± 11.7 years, and 8.4% had co-morbidities. AYUSH-64 was utilized as an add-on to the standard care by 58.3% of participants. Comparable clinical outcomes were observed in participants utilizing AYUSH-64 either as a standalone or as an add-on to standard care, in terms of clinical recovery, disease progression, the requirement for oxygen supplementation, hospitalization, ICU admission, and need for ventilator support. Younger age, having no co-morbidities or substance abuse, and having been vaccinated were associated with early clinical recovery than those who were older and not vaccinated.ConclusionsThe study findings suggest that AYUSH-64 use, either standalone or as an adjunct to standard care, in asymptomatic, mild, or moderate COVID-19 is associated with good clinical outcomes. Ayush services and interventions can be effectively integrated into the mainstream public health architecture to serve public health goals.